Factors associated with abdominal obesity and lipid alterations in low-income adults (Acta Scientiarum. Health Sciences, 2024)
To evaluate the prevalence of abdominal obesity, hypercholesterolemia and hypertriglyceridemia and its associated factors in adults in a low income region. Cross-sectional, population-based study with probabilistic sample representative of a region of the Brazilian Northeast. Abdominal obesity was determined by waist circumference â‰¥ 80cm for women and â‰¥ 94cm for men. The classification considered for hypercholesterolemia was cholesterol â‰¥ 240mgdL-1 and for hypertriglyceridemia, triglycerides â‰¥ 200mgdL-1. The Poisson regression analysis evaluated the association between abdominal obesity, serum lipid changes and explanatory variables. A number of 260 adults, of the economic level C and D/E (â‰…96%) were evaluated. The prevalence of abdominal obesity, hypercholesterolemia and hypertriglyceridemia were 71.5, 21.2 and 26.9%, respectively. There was an association between abdominal obesity and female gender, age 50-59 years, overweight, and brown/black race was related as a protection factor. Hypercholesterolemia, was associated with subjects aged 50-59 years and â‰¥ 60 years, and hypertriglyceridemia was associated with overweight, aged â‰¥ 40years and smoker individuals. High prevalence of abdominal obesity, hypercholesterolemia and hypertriglyceridemia were found. From the age of 40 the subjects already had a risk factor for hypertriglyceridemia and 50 years for hypercholesterolemia and abdominal obesity. Abdominal obesity was also associated with overweight female individuals, and the brown/black race was connected to a protective factor. Smoking and overweight were associated with hypertriglyceridemia.